Isolated primary agenesis of left lung presenting with recurrent respiratory infections - An uncommon presentation - Mohd Ilyas; Fahad Shafi; Kifayat Hussain Ganaie; Inayat Ellahi; Naseer Choh (SpringerOpen, 2018)
The present article reports a rare case of isolated primary left lung agenesis who presented with the history of recurrent respiratory infections. Lung agenesis is an uncommon entity resulting due to non-proliferation of the lung bud. The agenesis may be complete or partial depending upon the time of proliferative arrest. It may be isolated or associated with organ anomalies. In complete agenesis, there is no development of pulmonary vasculature or lung parenchyma, however, there may be rudimentary bronchus (as in the present case). The rudimentary bronchus becomes the site of impacted secretions which result in recurrent infections. The lung aplasia or hypoplasia may be primary or secondary. The secondary hypoplasia is due to some other anomalies like congenital diaphragmatic hernia which hampers the noemal development of the lung. The lung aplasia may be unilateral or bilateral. The bilateral lung aplasia is incompatible with life. The other anomalies which result due to maldevelopment of the lung buds include congenital trachea-esophageal fistula (further classified into five types depending upon the communication between the trachea and the esophagus), congenital lobar emphysema, congenital pulmonary airway malformation (earlier called congenital cystic adenomatoid malformation or CCAM), polyalveolar lobe, pulmonary arteriovenous malformation, intralobar or extralobar sequestration, pulmonary lymphangiectasia, and alveolocapillary dysplasia. The present report focusses only on the lung agenesis, its embryology, clinical manifestations and diagnosis. The various differentials of the lung agenesis include lung collapse, massive pleural effusion, and huge lung mass on radiography. The contrast-enhanced computed tomography plays the pivotal role in actual and accurate diagnosis of lung aplasia and helps in ruling out all differential diagnoses. Keywords: Lung agenesis, Recurrent infections, Computed tomography